IMPROVING STUDENT’S LEARNING OUTCOMES USING KAHOOT IN CLASS VII - Kusumawati, Upi Maelani (Prosiding Temu Ilmiah Nasional Guru, 2023)
Researchers as students as well as teachers in English subjects at Ar Rahman Bondowoso Middle School found the fact that the current English learning outcomes in class VII with a total of 8 students only 37.5% have basic abilities as expected in the Learning Objectives Achievement Criteria. This shows that the abilities obtained by students are still below the standard criteria set by the school. Researchers seek to improve learning by carrying out Classroom Action Research (CAR). The purpose of this research is to improve the English learning outcomes of students in Class VII Ar Rahman Middle School by using the Kahoot application. The results achieved in the improvement of Cycle 1 learning were still low at 62.4% but there were two students who improved from basic abilities to become proficient in English. There was an increase in the criteria for students who were proficient in English by 12%. The results of improving learning reached 87.5%. This means that student learning outcomes increase significantly.